Examining A Sports Mindset Program’s Impact On Executive Performance In Two Global Organisations - Conway, Michael (Digital Repository of Theses, 2025)
An innovative, integrated learning program focused on building more effective mindset skills and modelled on methods and concepts used in elite sports was examined to determine its impact on the performance of a sample of 20 senior leaders in 2 global organisations. The participants took part in a four-month-long online learning experience set within a unique virtual environment. This learning environment was engineered to help the participants develop their skills to achieve a "high-performance" mindset. A mixedmethods evaluation approach, using both qualitative and quantitative assessment tools, was employed to measure participant’s performance before, during and after their virtual learning experience. The outcome was evident: Participants and their leaders reported that the integrated mindset training improved things significantly at work and home. Surveys comprising four different metrics and two different sentiment analysis results also showed a positive trend. The researcher also built a new index, the Integrated Mindset Index, which was reviewed by elite sporting coaches from six sporting codes and the organisations leaders; the Index can be used to assess an individual’s progress in building an integrated mindset. At the very least, what happened in this research study sets a good precedent for the use of integrated mindset learning in organisational development strategies, particularly in achieving greater engagement and well-being of staff, both current and future. Fundamental in a competitive business world. This research study sheds light on how you can take the learning methodologies used in elite sports and adapt them to the world of executive education. It also confirms the vital importance of nurturing a growth-oriented mindset in business leaders if you want them and their teams to perform at peak levels. Further research is recommended with a larger cohort and control group over an extended period, to assess the impact of integrated mindset learning on organizational productivity, whilst also expanding the application of the Integrated Mindset Index and sentiment analysis.